Online teaching: a reflection. Issue 44 (2021) - Baddeley, Sam
Abstract : This article, written at the start of April 2021, is a personal reflection on what has and hasn't worked in remote/online education. I have drawn on my own experience of teaching over the course of the past year, observations of classroom practice I have undertaken as a mentor and middle leader with responsibility for teaching and learning in my school, and conversations I have had with colleagues in my school and elsewhere; it is, therefore, highly anecdotal, and the reader is asked to bear in mind the fact that, like many others, my journey into online teaching was enforced by the closure of schools during the first nationwide lockdown in March 2020. My core aim during both lockdowns was to provide for my students the best experience possible until such a time as we could all return to the physical classroom. As it became clear towards the end of 2020 and the start of 2021 that we were going to need to return to remote education, I began to think more deeply about the strategies I was employing in my online teaching, how effective they were for my students, and what I might do to maximise their learning experience and outcomes.